Loss of HER2‐positivity following neoadjuvant targeted therapy for breast cancer is not associated with inferior oncologic outcomes. Issue 8 (20th August 2021) - Wetzel, Catherine L.; Sutton, Thomas L.; Gardiner, Stuart; Farinola, Maryam; Johnson, Nathalie; Garreau, Jennifer R.
Abstract: Background: Patients with human epidermal growth factor receptor 2 (HER2)‐positive breast cancer are treated with trastuzumab‐based neoadjuvant therapy (NAT); some patients with residual disease post‐NAT show loss of HER2 amplification and has been inconsistently associated with oncologic outcomes. Methods: We queried our multi‐institutional cancer registry for women with HER2‐positive breast cancer undergoing NAT from 2011 to 2018. Clinicopathologic, treatment‐related, and outcomes data were collected. Kaplan–Meier and Cox proportional hazards analysis were used to evaluate oncologic outcomes. Results: A total of 348 patients were identified; 166 (48%) had a pathologic complete response. Of the 182 patients with residual disease, 87 (48%) were HER2‐positive, 34 (19%) were HER2‐negative, and 61 (33%) were HER2‐unknown, with a median follow‐up of 44 months. There were no factors associated with HER2 loss apart from age. On Kaplan–Meier analysis, estimated 5‐year recurrence‐free survival (RFS) and overall survival (OS) for patients with HER2‐positive residual disease was 81% and 92%, respectively, and 74% (log rank p = 0.75) and 81% ( p = 0.35) in patients with HER2‐negative residual disease. Conclusion: The loss of HER2‐positivity following NAT is not associated with worse 5‐year RFS or OS. We do not recommend retesting HER2 status following NAT for the purpose of clinical management; these patients should complete targeted adjuvant therapy.